The Transformations Of The Character Of Alan-Koa After The Expansion Of Islam - Khachatryan, Anush (ՀՀ ԳԱԱ)
The attention towards Islam and studies on the cross-cultural problems related to it has recently arisen, especially considering the role of Islam, the pivotal events happening in the Islamic world and growing interest in them. The main goal of this research is to reveal the similarities in Turko-Mongolian environment between the stories attributed to the Mongol foremother and the cornerstone, “bridging” figure in both Islam and Christianity, Virgin Mary.1 We intend to discuss the transformations of the character of Alan-Koa after the expansion of Islam based on written sources. Within the boundaries of the subject we set a goal to raise and solve the following problems: ● To try to analyze and understand the transformations of the character of Alan-Koa after the expansion of Islam ● To understand how these transformations took place and whether it was a result of manifestation of coexistence or not. ● Make a comparison between Mary and Alan-Koa uncovering the similarities between the stories attributed to them
Keywords: Ethnography